A Systematic Review of Postoperative Pain Outcome Measurements Utilised in Regional Anesthesia Randomized Controlled Trials - E. Pushpanathan; T. Setty; B. Carvalho; P. Sultan (Anesthesiology Research and Practice)
Introduction. Regional anesthesia is a rapidly growing subspecialty. There are few published meta-analyses exploring pain outcome measures utilised in regional anesthesia randomized controlled trials (RCTs), which may be due to heterogeneity in outcomes assessed. This systematic review explores postoperative pain outcomes utilised in regional anesthesia RCTs. Methods. A literature search was performed using three databases (Medline, Embase, and CINAHL). Regional anesthesia RCTs with postoperative pain as a primary outcome were included if written in English and published in one of the top 20 impact factor journals between 2005 and 2017. Study quality was assessed using the Cochrane Collaboration’s tool for assessing risk of bias. Results. From the 31 included articles, 15 different outcome measures in total were used to assess postoperative pain. The most commonly (16/31) used outcome measures were verbal numerical grading of pain out of 10, total opioid consumption, and visual analogue scale 10 cm (VAS). The need for analgesia was used as an outcome measure where studies did not use a pain rating score. Ten studies reported pain scores on activity and 27/31 studies utilised ≥2 pain outcomes. Time of measurement of pain score also varied with a total of 51 different time points used in total. Conclusion. Analysis of the articles demonstrated heterogeneity and inconsistency in choice of pain outcome and time of measurement within regional anesthesia studies. Identification of these pain outcomes utilised can help to create a definitive list of core outcomes, which may guide future researchers when designing such studies.